Identification and genomic profiling of a cotton leafroll dwarf virus isolate from Brownfield, TX - Verma, Pankaj Kumar; Watson, Branden H.; Sripathi, Venkateswara R.; Janga, Madhusudhana R. (Frontiers in Virology, 2025)
BackgroundCotton leafroll dwarf virus (CLRDV), a member of the Polerovirus genus, is an emerging pathogen that threatens global cotton (Gossypium hirsutum) production. Since its first detection in Alabama in 2017, CLRDV has spread rapidly to several states of the United States of America, including Texas.MethodsIn 2024, symptomatic cotton plants were collected from Brownfield, Texas. Total RNA was extracted, and RT-PCR was performed to amplify the viral genome and sequenced. The complete sequence (5,838 bp) was obtained and compared with existing CLRDV genomes from the U.S.ResultsThe Brownfield isolate displayed typical CLRDV genome features but also showed genetic differences compared to isolates from neighboring regions. Phylogenetic analysis indicated regional diversification, possibly due to environmental pressures or host cultivar variability.ConclusionThis study highlights the presence and evolution of CLRDV in Texas and neighboring states. Ongoing surveillance and development of resistant cotton cultivars are essential to mitigate yield losses.